2010
DOI: 10.1002/per.763
|View full text |Cite
|
Sign up to set email alerts
|

Self‐informant agreement for personality and evaluative person descriptors: Comparing methods for creating informant measures

Abstract: Little attention typically is paid to the way self-report measures are translated for use in self-informant agreement studies. We studied two possible methods for creating informant measures: (a) the traditional method in which self-report items were translated from the first- to the third-person and (b) an alternative meta-perceptual method in which informants were directed to rate their perception of the targets’ self-perception. We hypothesized that the latter method would yield stronger self-informant agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…However, patients with MCI and their informants had a lower mean agreement on personality ratings than patients with SCI and HC. Mean correlations for the SCI and HC dyads corroborate findings reported in earlier studies of self-other agreement according to the Big Five dimensions [14,21]. The result for the domain anxiety proneness/neuroticism was comparable to earlier findings, while extraversion showed lower correlations across groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, patients with MCI and their informants had a lower mean agreement on personality ratings than patients with SCI and HC. Mean correlations for the SCI and HC dyads corroborate findings reported in earlier studies of self-other agreement according to the Big Five dimensions [14,21]. The result for the domain anxiety proneness/neuroticism was comparable to earlier findings, while extraversion showed lower correlations across groups.…”
Section: Discussionsupporting
confidence: 89%
“…Characteristics of the situation, the person being judged and the judge have also been correlated to agreement [18,19,20]. Furthermore, the personality literature has demonstrated a higher degree of self-other agreement for ratings of visible, extraverted, behaviors compared to more affective personality traits [21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, wives tended to report higher pathology for themselves on traits within the Negative Affectivity domain, whereas husbands reported more pathology for themselves on traits within the Antagonism and Disinhibition domains. South et al (2011) andSimms et al (2010) found similar results, with spouses typically reporting more negatively for themselves and more positively for their respective spouses. This tendency to report less pathology for spouses may reflect the letter of recommendation effect described by Leising, Erbs, and Fritz (2010), where raters are apt to provide more positive reports if they like the target being rated.…”
Section: Spousal Agreementmentioning
confidence: 63%
“…Although a thorough review is beyond the scope of this manuscript, researchers have found a wide range of agreement between target and informant ratings ( r s ranging from .25 to .62; Simms et al, 2010). Multiple factors influence the degree of association such as how visible (i.e., overt) the traits are, type/length of relationship with the informant rater, size of the sample, and age of the sample (Coolidge, Burns, & Mooney, 1995; Watson et al, 2000).…”
mentioning
confidence: 99%
“…Importantly, though limited information is available regarding agreement on symptoms of depression and anxiety, vast research has been completed in the adult literature on personality and personality disorders (e.g., Klonsky et al, 2002; Simms, Zelazny, Yam, & Gros, 2010; Watson, Hubbard, & Wiese, 2000). Although a thorough review is beyond the scope of this manuscript, researchers have found a wide range of agreement between target and informant ratings ( r s ranging from .25 to .62; Simms et al, 2010).…”
mentioning
confidence: 99%